Perceptions of the Local Food Environment and Experiences with Food Access Among Low Income Rural Louisiana Residents. (29th May 2020) - Holston, Denise; Greene, Matthew; Stroope, Jessica
Abstract: Objectives: The purpose of this exploratory study was to describe perceptions of the local food environment and factors related to food access among low-income residents in rural, high-poverty parishes (counties) in Louisiana. Methods: Data were primarily collected from four focus group discussions (FGD). Participants were low-income residents of high poverty, rural parishes and participating in at least one public assistance program. Subjects provided consent and completed a food access survey prior to participation. The FGD questions were based on rural food access literature and study objectives. During the FGD, participants were asked about their perceptions of the local food environment and local food access, how they acquired food, barriers to food access and possible solutions to address perceived barriers. FGD were transcribed verbatim and coded and themed by independent coders. Results: 24 low-income adults participated in the FGD. 96% of participants were Black and 25% were male. Almost half (42%) reported not having enough food per month and 62% (n = 15) reported running out of food before the end of the month. Almost all participants reported that price was the most important factor when shopping for food. The majority of participants, especially in 2 parishes, thought the cost of food was too high at stores within the parish. Barriers to access to foods included cost, transportation, and not having enough benefits or money to cover monthly food costs. The majority of participants, especially in 2 parishes, traveled 30 or more miles to grocery stores for perceived reasonable prices and quality food. Transportation for monthly shopping trips came at a price of 10–40 per trip. Participants in one isolated parish traveled to other parishes for specific items. Participants reported shopping at 2–4 stores monthly based on sales. Participant- derived solutions to food access were few but included locally owned grocery stores and local, public transit to foods stores for better prices. Conclusions: Food access for low-income individuals living in rural locations is complex and contributes to food insecurity observed in this population. Public transit to grocery stores with low prices may be a solution to food access challenges in rural areas. Funding Sources: Centers for Disease Control NU58DP006570.